Report of the court proceedings. The case of the Trotskyite-Zinovievite terrorist centre. Heard before the military collegium of the supreme court of the U.S.S.R. Moscow, August 19-24, 1936. In re G.E. Zinoviev, L.B. Kamenev, G.E. Evdokimov, a.o. Charged under articles 58-8, 19 an 58-8, 58- 11 of the criminal code of the R.S.F.S.R (Moscow, 1936)
Publ. by the People's commissariat of justice of the U.S.S.R.